Aplikasi Teknologi RFID pada E-Rekam Medis untuk Manajemen Posyandu Berbasis Web - Tyas Aprilia; Nugroho Suharto; Lis Diana (Jurnal Jaringan Telekomunikasi, 2020)
The current measurement process in posyandu generally done manually, i.e. when the user arrives, measurement will be taken then the data stored manually on paper. This system is considered inefficient because it’s need a long time, causing long queues and possibility of stacked data storage. From several problems indications that have been found, it’s necessary to develop a system that makes posyandu and midwives work quickly and accurately. Therefore, it’s necessary to develop technology that aims to create new system. This study uses Arduino as microcontroller and raspberry pi as server, there's node, inside the node there's an ultrasonic sensor to determine height, then load cell sensor to determine the user's weight. Data will be sent from Arduino Uno to NRF, on server there's NRF24L01, the server used a raspberry pi 3. The client server communication technique is designed for communication between nodes and servers so that data transmission errors are smaller. Based on  test results, it’s known that RFID has maximum detection distance limit of 3cm with a maximum detection delay of 2.9s. In medical e-record system, the load cell sensor has an error deviation of 3.48% and the ultrasonic sensor is 1.129%. The data can be displayed on the application includes the toddler's name, weight and height. Based on the test results, it‘s known that the accuracy of data communication has the best packet loss value of 0%, the worst packet loss value is 0.18%, the best delay value is 0.1s and the worst delay value is 4.1s.